An Assessment on Technologies for Implementing Core Assets in Service-Oriented Product Lines - Ribeiro, Heberth Braga G.; Meira, Silvio Romero de Lemos; Almeida, Eduardo Santana de; Lucrédio, Daniel; Álvaro, Alexandre; Alves, Vander; Garcia, Vinicius Cardosp (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS), 2010)
Software Product Lines (SPL) and Service-Orientation (SO) are two strategies that focus on different goals, but they both use software reuse as their main principle. SPL encompass a family of software systems developed from reusable assets, while SO is a way of developing service-based applications, providing reusable business functionalities. In the combination of SPL and SO, a key aspect is the understanding about the use of variability mechanisms for realizing variabilities in different levels of granularity (e.g., components, services, service-orchestrations) addressed in a technology specific way and improve modularity, complexity, and Separation of Concerns (SoC) of reusable assets. In this paper, we present a quantitative case study for evaluating the modularity, complexity, SoC and stability of reusable core assets using distinct technologies for implementing them, and an initial decision model based to guide software engineers on choosing suitable technologies.